Analisis Kemampuan Penalaran Statistis Siswa pada Materi Penyajian Data Berkelompok Ditinjau dari Self Confidence Siswa - Lina Lina; Desi Rahmatina; Mariyanti Elvi (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2024)
This research aims to analyze students' statistical reasoning processes in group data presentation material in terms of students' self-confidence. This research is a type of research, namely descriptive qualitative. Because this research will describe students' statistical reasoning processes in group data presentation material in terms of students' self-confidence. The subjects of this research were 29 students of class XII MIPA 4 SMA Negeri 4 Tanjungpinang who were then narrowed down to 2 students representing each self-confidence categori, namely high self-confidence, medium self-confidence, and low self-confidence. The results of this research were that there were 5 students who had high self-confidence, 20 students who had moderate self-confidence, and 4 students who had low self-confidence. Students who have high self-confidence and moderate self-confidence meet all indicators of statistical reasoning, while students who have low self-confidence do not meet all indicators of statistical reasoning.